Limitations Of Pert/Cpm In Construction Management Planning: Inputs To Mathematics In Architecture Education - et. al., Lexphil John B. Ragel, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research identified the roadblocks or shortcomings of PERT/CPM in the context of a construction company and suggested a plan to address the identified gaps. The researchers used a descriptive research design to discover the shortcomings of the PERT/CPM in construction management planning, especially in the Cabanatuan City, Nueva Ecija, Philippines construction industry. As a result, PERT/CPM is a project management approach that is useful in the basic administrative functions of planning, scheduling, and control. These days, business houses undertake massive projects that take years to complete before commercial development can begin. While this tool can be very useful, the majority of respondents agreed that it has limitations, such as; PERT/CPM can become ineffective and difficult to manage if it is not well-defined and stable for active control of a project; PERT/CPM requires frequent updating and revising of calculations, which is an extensive and time-consuming exercise that requires highly specialized knowledge; PERT/CPM requires frequent updating and revising of calculations, which is an expansive and time-consuming exercise that requires highly specialized knowledge; Furthermore, it is unable to efficiently accommodate abrupt shifts in the ground plan's execution. However, despite its limitations, PERT/CPM is still recommended for construction management planning, especially in large projects. The project manager must always have a contingency plan in place so that the quality of his or her work and projects won’t be jeopardized. In order to make the best use of all available resources in their production, a cost-benefit analysis must be performed, as well as additional research about PERT/CPM. The study's findings have implications for mathematics education in architecture.